Insights into changing coastlines, environments and marine hunter-gatherer lifestyles on the Pacific coast of South America from the La Yerba II shell midden, Río Ica estuary, Peru - Beresford-Jones, David G. (2022)
Fil: Beresford-Jones, David G. University of Cambridge; Reino Unido.